2012
DOI: 10.1007/s00018-012-0928-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton responses in wound repair

Abstract: Wound repair on the cellular and multicellular levels is essential to the survival of complex organisms. In order to avoid further damage, prevent infection, and restore normal function, cells and tissues must rapidly seal and remodel the wounded area. The cytoskeleton is an important component of wound repair, needed for actomyosin contraction, recruitment of repair machineries, and cell migration. Recent use of model systems and high-resolution microscopy has provided new insight into molecular aspects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 91 publications
(145 reference statements)
3
90
0
1
Order By: Relevance
“…Our results suggest that OA-induced EphB2 expression mediates the downstream signal pathways involved in the activation of Rac1; however, the precise mechanism requires further investigation. Furthermore, a cytoskeletal rearrangement accompanies stem cell migration to an injury site in response to wound-healing mediators such as proinflammatory cytokines, chemokines, and angiogenic factors [56,57]. We observed that an OA pretreatment improved the migration ability of UCB-MSCs and increased the number of UCB-MSCs at wound sites.…”
Section: Discussionmentioning
confidence: 85%
“…Our results suggest that OA-induced EphB2 expression mediates the downstream signal pathways involved in the activation of Rac1; however, the precise mechanism requires further investigation. Furthermore, a cytoskeletal rearrangement accompanies stem cell migration to an injury site in response to wound-healing mediators such as proinflammatory cytokines, chemokines, and angiogenic factors [56,57]. We observed that an OA pretreatment improved the migration ability of UCB-MSCs and increased the number of UCB-MSCs at wound sites.…”
Section: Discussionmentioning
confidence: 85%
“…16 GTPase activated Rho-associated coiled-coil kinases (ROCKs) are key regulators of cytoskeletal rearrangement through the regulation Lin11, Isl-1, Mec-3 (LIM) kinase/cofilin activity. 17 LIM domain proteins are also known to regulate transforming growth factor-β (TGF-β) signaling and affect EMT in wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,24 MT stabilizers, destabilizers, and motors are emerging as regulatory components of the migration machinery of cells. 9,25,26 A summary of key MRPs and their various functions is presented in Table 1.…”
mentioning
confidence: 99%